Active disturbance rejection attitude control for a hypersonic reentry vehicle with actuator saturation. (3rd May 2017) - Yang, Hongjiu; Yu, Yang; Wang, Fang; Lu, Kunfeng
In this article, nonlinear uncertainty has been investigated for a hypersonic reentry vehicle subject to actuator saturation via active disturbance rejection control technology. A nonlinear extended state observer is designed to estimate "total disturbances, " which is compensated with a linear controller. Both convergence of the nonlinear extended state observer and stabilization of the closed-loop system are studied in this article. Some simulation results are given to illustrate the effectiveness of the proposed method.